2002
DOI: 10.1007/s10162-002-3015-9
|View full text |Cite
|
Sign up to set email alerts
|

The Deaf Mouse Mutant Jeff (Jf) is a Single Gene Model of Otitis Media

Abstract: Otitis media is the most common cause of hearing impairment in children and is primarily characterized by inflammation of the middle ear mucosa. Yet nothing is known of the underlying genetic pathways predisposing to otitis media in the human population. Increasingly, large-scale mouse mutagenesis programs have undertaken systematic and genomewide efforts to recover large numbers of novel mutations affecting a diverse array of phenotypic areas involved with genetic disease including deafness. As part of the UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 30 publications
3
79
0
Order By: Relevance
“…Significant P-values are shown in bold, those approaching significance are shown in italics. On a C3H/HeH background, 9 Jf homozygous mutant mice have severe developmental defects, including cleft palate, which is a developmental condition known to increase the prevalence of OM in humans, 15 whereas heterozygous Jf/ þ mice demonstrate mild craniofacial abnormalities, such as a shortened snout and smaller eustachian tubes. Whilst these craniofacial abnormalities may contribute to the OM susceptibility observed in these mice, it has been shown that on a C57BL/6 background Jf/ þ mice have no apparent craniofacial defects although they do still develop OM (SD Brown, unpublished data 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant P-values are shown in bold, those approaching significance are shown in italics. On a C3H/HeH background, 9 Jf homozygous mutant mice have severe developmental defects, including cleft palate, which is a developmental condition known to increase the prevalence of OM in humans, 15 whereas heterozygous Jf/ þ mice demonstrate mild craniofacial abnormalities, such as a shortened snout and smaller eustachian tubes. Whilst these craniofacial abnormalities may contribute to the OM susceptibility observed in these mice, it has been shown that on a C57BL/6 background Jf/ þ mice have no apparent craniofacial defects although they do still develop OM (SD Brown, unpublished data 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional data from mouse models, 8,9 combined with Ingenuity pathway analysis (Ingenuity Systems, http://www.ingenuity.com), indicated that both gene products interact with the TGFb pathway and thus other key genes in this pathway-SMAD2, SMAD3, SMAD4 and SMAD7-were also investigated. For genotyping in the family cohort, a minimum of two haplotype tagging (tag) SNPs were selected for each gene using data from the Caucasian population in the International HapMap Project.…”
Section: Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Middle ear inflammation and increased otitis media susceptibility have been observed in mice with mutations in Eya1, Six1, and Fbxo11 (27,(30)(31)(32). To determine whether Eya4 -/-mice developed otitis media because these genes were dysregulated by the absence of Eya4, we compared expression in wild- The moET, isthmus, cartilaginous segment (cartET), and opening of the eustachian tube within the nasopharynx (OpNP) are indicated on the wild-type 3D reconstruction.…”
Section: Production Of Eya4-deficient Mice the Endogenous Eya4 Gene Wasmentioning
confidence: 99%
“…In addition to genetically engineered mouse models, chemical mutagenesis using N-ethyl-N-nitrosourea (ENU), which causes primarily single-nucleotide mutations, has produced numerous new mouse models for studying human disease. Many of these mutants carry a novel functional mutation in a known gene (7)(8)(9)(10)(11). For known genes, having multiple models with a variety of unique mutations allows a survey of phenotypic differences and functional annotation of genes and their products.…”
mentioning
confidence: 99%